FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PASAR TENAGA KERJA DAN IMPLIKASI KEBIJAKANNYA TERHADAP SEKTOR PERTANIAN DI KABUPATEN BOGOR - HERMANTO SIREGAR; TATAN SUKWIKA (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2007)
There has been a general concern that after the implementation of the regionalautonomy policy, the labor market performance tenfing to decline. This paper aims atanalysing various factors influencing the labour market, by making use of aneconometric model of simultaneous equation system employing a set of pooled or paneldata (combination of yearly time series and 30 subdistricts cross section in BogorRegency). The results showed that estimated parameters accord well with the theory.The estimated model is fairly good to explain the variation of labor market of BogorRegency, prior to as well as during the ongoing regional autonomy period. Among theresults, it is found that, in agricultural and service sectors, employment absorption foreducated and uneducated labours is higher during the autonomy than before theautonomy. The opposite happens in the industrial sector. In all sectors, investmentplays an important role in determining employment absorption. Together with labourproductivity, employment absorption positively affects gross domestic regionalproduct, which in turns influences a number of labour market variables.